2012
DOI: 10.1088/1468-6996/13/1/015002
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and antibacterial activity of superparamagnetic nanoparticles modified with glycol chitosan

Abstract: Iron oxide nanoparticles (IONPs) were synthesized by coprecipitation of iron salts in alkali media followed by coating with glycol chitosan (GC-coated IONPs). Both bare and GC-coated IONPs were subsequently characterized and evaluated for their antibacterial activity. Comparison of Fourier transform infrared spectra and thermogravimetric data of bare and GC-coated IONPs confirmed the presence of GC coating on IONPs. Magnetization curves showed that both bare and GC-coated IONPs are superparamagnetic and have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(21 citation statements)
references
References 33 publications
(88 reference statements)
3
18
0
Order By: Relevance
“…30 Moreover, iron oxide nanoparticles have been shown to generate ROS when interacting with bacteria, resulting in protein oxidation and cell death. 31,32 Additionally, E. coli cells were observed to be divided into two parts after being in contact with the sharp FBP edge (Fig. S18e and f †), demonstrating physical damage.…”
Section: Disinfection Effectmentioning
confidence: 97%
“…30 Moreover, iron oxide nanoparticles have been shown to generate ROS when interacting with bacteria, resulting in protein oxidation and cell death. 31,32 Additionally, E. coli cells were observed to be divided into two parts after being in contact with the sharp FBP edge (Fig. S18e and f †), demonstrating physical damage.…”
Section: Disinfection Effectmentioning
confidence: 97%
“…Moreover, the mixture of AgNPs with chitosan was stirred and mixed overnight, the chitosan-AgNPs (CS-AgNPs) were recovered using centrifuge. 23…”
Section: Synthesis Of Agnps Using Rosa Damascenes Extractmentioning
confidence: 99%
“…Hydrophilic negatively charged particles showed insignificant antibacterial activity, while modulation of surface functional group to impart a strong positive charge (e.g., ATPMS-MNPs; 24.5 mV) enhanced the antibacterial activity [8,54,55]. This indicated that surface positivity imparts antibacterial potential on the particles.…”
Section: Mnps ( G/ml)mentioning
confidence: 99%